Segmental osteotomy, implants, and restorative procedures for the treatment of an extruded maxillary alveolar segment - Sanket Gavhane; Godwin Clovis Da Costa; Paul Chalakkal; Neil De Souza (Wolters Kluwer Medknow Publications, 2019)
This case report highlights a case of full-mouth rehabilitation in a 38-year-old female. Extrusion of the right posterior maxillary alveolar segment had resulted due to the presence of an opposing edentulous mandibular span, which had led to complete absence of restorative space in the lower arch. Maxillary posterior segmental osteotomy was carried out to obtain adequate space for placing an implant-supported prosthesis in the opposing edentulous mandibular span. The procedures before the surgery consisted of articulation of the diagnostic casts on to a semi-adjustable Hanau™ Wide-Vue articulator and a mock surgery on the upper cast to assess the amount of segmental osteotomy necessary to accommodate an implant-supported prosthesis in the lower edentulous region. Other procedures included implant placements, root canal treatment, post and core build-up, and full-crown placement on various teeth.